Relevancy of Kufic Scripts In Wayfinding And Signage of Public Buildings In The Urban Scape of Selangor - Zumahiran Kamarudin; Raja Intan Suhaylah Raja Abdul Rahman (Universitas Negeri Malang, 2021)
The development of Kufic calligraphy has some impact on the graphic art of the wayfinding design. However, information on the Kufic styles used in the wayfinding design and signage is little known, and studies about this aspect are minimal. Therefore, the objectives of this study are to identify and analyse the different styles of Kufic scripts used in the wayfinding design and signage and to categorise and characterise Kufic calligraphy's application for the wayfinding design of commercial and institutional buildings in the urban scape of Selangor. This research involved a visual analysis of the wayfinding design and signage of 10 visited buildings to get more accurate screening on the types and styles of Kufic scripts used. The analysis revealed the application of three major Kufi styles in the different location of wayfinding signage of the buildings suggesting the relevancy of angular calligraphy for wayfinding design and signage.